DIGITAL APPROACHES TO TEACHING THE LITERATURE OF THE TARGET LANGUAGE COUNTRY IN EFL CLASSROOMS - Khusenoova Mehriniso Uktamovna (International Journal of Literature and Language Studies, 2026)
The integration of digital technologies into English language education has transformed the way literature is taught in English as a Foreign Language (EFL) classrooms. Traditional literature instruction, which mainly relied on printed texts and teacher-centered explanations, is gradually being replaced by interactive, technology-enhanced approaches that foster learner engagement, critical thinking, and intercultural awareness. This paper examines the effectiveness of digital approaches to teaching the literature of the target language country by reviewing current pedagogical strategies and digital tools used in EFL contexts. It discusses the application of digital storytelling, e-books, learning management systems, online discussion platforms, artificial intelligence, and multimedia resources in literature instruction. The paper argues that digital technologies not only improve learners’ literary competence but also contribute to language proficiency, collaborative learning, and autonomous study. Furthermore, the study highlights the challenges teachers encounter, including limited digital literacy, unequal access to technology, and the need for professional development. The findings indicate that integrating digital tools into literature teaching creates more interactive learning environments and enhances students’ motivation and interpretation of literary texts.